Digitalisasi UMKM Desa Turunrejo: Transformasi Pembayaran menuju Era Modern - Yuliyanti, Eka; Turmudhi, Anis; Kartika, Andi; Fadhila, Zati Rizka; Rosyid, Azis Nur (Global Health Science Group, 2024)
Program pengabdian masyarakat bertema